Effects of Male International Migration on Mental Health of Wives Left Behind in Nepal - Bhirtyal, Yagya Murti; Wasti, Sharada Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
Introduction: International male migration is very common and has been increasing significantly in recent days in Nepal.The increasing pattern of male migration has greatly impacted left-behind women. The aim of the study was to assess the effects of male international migration on the mental health (depression) of wives left behind in Nepal. Methods: A cross-sectional study was conducted with a total of 800 women (400 wives left behind and 400 wives of non-migrants) in the Chitwan district of Nepal.A systematic random sampling approach was employed for the recruitment of study respondents.Data were collected through a structured questionnaire with face-to-face interviews.Depression was measured by using a valid tool of depression screening questionnaire consisting of a 20-items scale. Data were managed in SPSS version 19 and analysed with a descriptive statistic followed bylogistic regression analysis. Ethical approval was obtained from the Nepal Health Research Council and individual written consent was obtained prior to the interview. Findings: The prevalence of depression in left-behind wives was 79 percent whereas only a 26.3 percent prevalence rate was found in the wives of non-migrants. There was a significant difference in depression between left-behind wives and the wives of non-migrants. The left-behind wives (OR = 10.57, p < 0.001) had around 11 times greater odds of having depressive symptoms compared to the wives of non-migrants. Logistic regression shows that theCaste/ethnicity (OR 1.15), level of education (OR 2.4), own named property (OR 1.7), and having children (OR 8.39) were identified as factors influencing depression in left-behind wives. However, the age of the wives (OR 0.46), level of education (OR 1.77), and employment status (OR 1.7) were found as factors that influence the depression in the wives of non-migrants. Findings between the left-behind wives and the wives of non-migrants depict that only women’s education (OR 2.94 vs 1.77) was found to be significantly associated with depression in both groups. Conclusions: The increasing trend of male international migration has negative effects on left-behind wives regarding health and wellbeing. There should have targeted intervention mental health screening and counselling programs forboth non-migrant and left-behind wives for early detection and treatment. Government should plan psychosocial counselling clinics and awareness-raising programmes particularlyto the higher male migration communities for early detection and treatment.